Understanding Mathematically Talented Male Learners’ Perception of Teaching Mathematics as a Profession: A Path Analysis - Calibara, Kim Jann A.; Belarga, Alona M. (Future Science / FSH-PH Publications, 2024)
ABSTRACT This descriptive-correlational research aimed to examine the predictive and mediational role of parental support, classroom environment, value, attitude, and anxiety in the perception towards teaching mathematics as a profession of mathematically talented male senior high school learners. One hundred eighteen learners from purposively selected public and private schools in Iloilo City and in the districts of the province of Iloilo participated in the study. Six adapted instruments were used to gather data, which underwent content validation and reliability testing. Means, frequency, standard deviations, Pearson’s product-moment correlations, Multiple Linear Regression and Path Analysis, were the statistical tools used. Results revealed that mathematically talented male learners have moderate parental support, a positive classroom environment, a very useful value of mathematics, a strongly positive attitude, low anxiety, and a moderately high perception towards teaching mathematics. When classified according to parental support, learners who received moderate and high parental support outscored learners with low parental support in their attitude towards mathematics and perception towards teaching mathematics. Also, learners in the positive group outperformed learners in the slightly positive group in their attitude towards mathematics when classified according to the classroom environment. Parental support, value, and attitude can directly predict the perception towards teaching mathematics, but not classroom environment and anxiety. Moreover, parental support, value and attitude were partially mediated while classroom environment was completely mediated on the influence the perception towards teaching Mathematics by the other constructs included in the model. Furthermore, the classroom environment influences the perception towards teaching mathematics. Parental support has the highest contribution in predicting the perception towards teaching mathematics. In conclusion, these findings indicated that parental support has the biggest attribution in predicting mathematically talented male learners’ perceptions towards teaching mathematics.